2017
DOI: 10.1111/cea.12867
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in the diagnosis of asthma in adults: a systematic review

Abstract: Summary Objectives To identify and synthesize evidence on the diagnostic accuracy of FENO for asthma in adults. Materials and Methods Systematic searches (nine key biomedical databases and trial registers) were carried out on November 2014. Records were included if they recruited patients with the symptoms of asthma; used a single set of inclusion criteria; measured FENO50 in accordance with American Thoracic Society guidelines, 2005 (off‐line excluded); reported/allowed calculation of true‐positive, true‐nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
(168 reference statements)
0
7
0
2
Order By: Relevance
“…10 Therefore, elevated FeNO is assumed to reflect an eosinophilic asthma phenotype, which account for approximately 50% of all asthmatics seen in clinical practice although higher in children. 16,17 Asthma monitoring FeNO has been proposed as a biomarker that may help the clinician to manage asthma. 10 Combining FeNO and peripheral eosinophil counts seems to be a better approach than just using FeNO values.…”
Section: Exhaled Breathmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Therefore, elevated FeNO is assumed to reflect an eosinophilic asthma phenotype, which account for approximately 50% of all asthmatics seen in clinical practice although higher in children. 16,17 Asthma monitoring FeNO has been proposed as a biomarker that may help the clinician to manage asthma. 10 Combining FeNO and peripheral eosinophil counts seems to be a better approach than just using FeNO values.…”
Section: Exhaled Breathmentioning
confidence: 99%
“…15 However, it should be always be kept in mind that asthma cannot be ruled out when symptoms are compatible with the condition despite low values of FeNO, as asthma is not necessarily eosinophilic. 16,17 Asthma monitoring FeNO has been proposed as a biomarker that may help the clinician to manage asthma. 18,19 FeNO values above 33 ppb in one study 20 and above 47 ppb in another 21 were found to predict a good clinical response to ICS in patients with chronic respiratory symptoms.…”
Section: Exhaled Breathmentioning
confidence: 99%
“…The second paper conducted a systematic review of 27 studies to assess the diagnostic accuracy of the fraction of NO in exhaled breath. 162 This test, which can be performed using a hand-held monitor, may provide an indicator of eosinophilic inflammation of the airways. Diagnostic accuracy was found to be highly variable, and the results imply that more work is needed using well-designed studies to determine the suitability of this test within the asthma diagnosis pathway.…”
Section: Immunotherapymentioning
confidence: 99%
“…Exhaled nitric oxide measurements is creeping in as part of the routine care in the asthma clinic . It is therefore important to understand the factors that can change levels, outside of asthma.…”
mentioning
confidence: 99%